2014
DOI: 10.19173/irrodl.v15i5.1850
|View full text |Cite
|
Sign up to set email alerts
|

Writing to learn and learning to write across the disciplines: Peer-to-peer writing in introductory-level MOOCs

Abstract: <p>This study aimed to evaluate how peer-to-peer interactions through writing impact student learning in introductory-level massive open online courses (MOOCs) across disciplines. This article presents the results of a qualitative coding analysis of peer-to-peer interactions in two introductory level MOOCs: English Composition I: Achieving Expertise and Introduction to Chemistry. Results indicate that peer-to-peer interactions in writing through the forums and through peer assessment enhance learner unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
5
27
0
10
Order By: Relevance
“…Understanding overall attitude is important because of the reported link between positive educational climates and increased student motivation for learning and academic achievement (Cohen, McCabe, Michelli, & Pickeral, 2009). The attitude of the interviewee statements was more positive than negative, indicating that MOOCs offer a constructive learning environment with manageable levels of frustration; this supports the findings of previous work examining the attitude of student writing on MOOC forums (Comer et al, 2014). The qualitative analysis described in the next section provides a more detailed portrayal of how students responded to each individual question, providing the authentic voice of the students and allowing for more in-depth inferences on what facilitates a better atmosphere for students in MOOCs.…”
Section: Sentiment Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Understanding overall attitude is important because of the reported link between positive educational climates and increased student motivation for learning and academic achievement (Cohen, McCabe, Michelli, & Pickeral, 2009). The attitude of the interviewee statements was more positive than negative, indicating that MOOCs offer a constructive learning environment with manageable levels of frustration; this supports the findings of previous work examining the attitude of student writing on MOOC forums (Comer et al, 2014). The qualitative analysis described in the next section provides a more detailed portrayal of how students responded to each individual question, providing the authentic voice of the students and allowing for more in-depth inferences on what facilitates a better atmosphere for students in MOOCs.…”
Section: Sentiment Analysissupporting
confidence: 85%
“…The affective domain has been investigated through qualitative methods examining student writing in assignments and on discussion forums in MOOCs (Comer, Clark, & Canelas, 2014). Motivation to learn in MOOCs has recently been studied from various perspectives, such as by examining aspects of language and social engagement (Barak, Watted, & Haick, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This result shows a similarity with the results gained in the previous studies [55][56][57][58][59][60][61][62][63]. It was observed that; EG1 had higher pre scores and better attitudes whereas EG2 showed an improvement but the difference was not statistically significant.…”
Section: Resultssupporting
confidence: 90%
“…The results concerning the academic success of the students reveal out a parallelism with the studies conducted by making use of the WTL activity (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Considering the values obtained at the end of the research, it was found that; the students who were taught the SPT through the letter writing activity, which is one of the WTL activities, became more successful than the students who were taught through the traditional teaching method.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation